Archaeology and Archaeometry of Ceramics of the Roman City of Thaenae (Tunisia): between Inland Roman Africa and the Mediterranean Basin - (:unkn) unknown (My University, 2018)
This research project is about the archaeological and archaeometric characterization of African ceramics. The development of a combined archaeological, petrographic and geochemical approach is currently one of the most promising approaches for the determination of ancient ceramic productions and their tracing throughout the Mediterranean basin. Tested on the collection of African Red Slip wares of the Museum of Gap (France), this interdisciplinary method is currently tested on the ceramic material of the Ancient city of Thaenae/Thyna (Tunisia). This integrated study aims to provide a characterization of the pottery production specific to the Thaenae site, to measure its diffusion in the Mediterranean basin and to determine the economic role of Thaenae during late antiquity. The development of rigorous protocols will allow the application of this approach to other ceramic productions in the Mediterranean basin.
Keywords: African Research